A Preliminary Literature Review on the Effect of Immigration On Australian Domestic Employment and Wages. (17th May 2022) - Boucher, Anna; Breunig, Robert; Karmel, Cecilia
Abstract: The effects of immigration on domestic Australian employment levels and wages are ongoing and controversial topics. While this topic has been considered extensively in other countries, in particular the United States and the United Kingdom, these findings have limited application to Australia given differences in immigration settings between these contexts. We review the existing literature and conclude that further research in the Australian context is needed given its high rates of both permanent and temporary immigration, its complex visa structure, the unusual nature of its industrial relations system and the geographical concentration of its population. In particular, more attention to the temporary migrant population is required in future studies .